A Novel Electronically Controlled Two-Dimensional Terahertz Beam-Scanning Reflectarray Antenna Based on Liquid Crystals - Yang, Jun; Wang, Pengjun; Sun, Shuangyuan; Li, Ying; Yin, Zhiping; Deng, Guangsheng (Frontiers in Physics, 2020)
This study investigated a novel electronically controlled two-dimensional beam-scanning reflective array antenna (reflectarray), which uses nematic liquid crystals. A double-dipole resonance structure is used as the phase-shift unit for the reflectarray for the required phase compensation. The simulation shows that, for about 7 GHz bandwidth of the phase shift range, over 360° can be achieved at the F-band. In addition, a novel wiring scheme is proposed to reduce the adverse effect of the biasing line on the phase-shift performance and simplify the manufacturing process. A simulation of the designed 39 × 39 reflectarray shows that the maximum beam steering range, maximum gain, and side-lobe level at 115 GHz are 20°, 16.55 dBi, and -8.4 dB, respectively.